C12‐Helix Development in (αγ)n Sequences – Spectroscopic Characterization of Boc–[Aib–γ4(R)Val]–OMe Oligomers. Issue 17 (14th May 2013) - Dinesh, Bhimareddy; Vinaya, Vishwanathan; Raghothama, Srinivasarao; Balaram, Padmanabhan
Abstract: The solution conformations of the αγ‐hybrid oligopeptides Boc–[Aib–γ 4 ( R )Val] n –OMe ( n = 1–8) in organic solvents have been probed by NMR, IR, and CD spectroscopic methods. In the solid state, this peptide series favors C12 ‐helical conformations, which are backbone‐expanded analogues of 310 helices in α‐peptide sequences. NMR studies of the six‐ ( n = 3) and 16‐residue ( n = 8) peptides reveal that only two NH protons attached the N‐terminus residues Aib(1) and γ 4 ( R )Val(2) are solvent‐exposed. Sequential N i H–N i +1 H NOEs characteristic of local helical conformations are also observed at the α residues. IR studies establish that chain extension leads to a large enhancement in the intensities of the hydrogen‐bonded NH stretching bands (3343–3280 cm –1 ), which suggest elongation of intramolecularly hydrogen‐bonded structures. The development of C12 ‐helical structures upon lengthening of the αγ sequence is supported by the NMR and IR observations. The CD spectra of the (αγ) n peptides reveal a negative maximum at ca. 206 nm and a positive maximum at ca. 192 nm, spectral feature that are distinct from those of 310 helices in α‐peptides. Abstract : The formation of C12 ‐helical structures in the hybrid αγ oligopeptides Boc–[Aib–γ 4 ( R )Val] n –OMe in solution is demonstrated by NMR and IR methods. The intramolecularly hydrogen‐bonded solution conformations resemble those previously determined by X‐ray crystallography. C12 ‐helix development has also been monitored by far‐UV CD.